Efektivitas Mendongeng Untuk Meningkatkan Pemahaman Respek Kepada Lingkungan Pada Anak Usia 5-6 Tahun - Melissa Tuanakotta; Wahyu Indianti (Universitas Islam Indonesia, 2018)
In today's modern society, including in Indonesia, there is an environmental crisis. This environmental crisis can be overcome by changing people's behavior and perspective by intervening to the community as early as possible. Storytelling can be one way to increase children's understanding about respect for nature. This study aims to knowing the effectiveness of storytelling to increase understanding of respect for nature in children aged 5-6 years. This study involving 31 children from TK Negeri Pembina, Kuningan, as participants. Intervention is done by reading four tales in four days. Understanding of respect for nature is measured using a measurement tool created by the researcher, in the form of six illustrations that depicting the behavior of respect for nature. The statistic analysis using Wilcoxon signed-rank test showed the difference of mean value of respect for nature understanding is significant (p <0.05) between before and after reading tales. The result of post-test 2, which done two weeks after the intervention still shows an increase score from the pre test.